SAW Filter Modelling in Matlab for GNSS Receivers - Syed Haider Abbas; Hussnain Haider; Muhammad Faheem Siddique; Awais Ahmed (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Satellite navigation has enabled a great amount of new application for many users, but a lot of limitations have been observed regarding precision and integrity of navigation signals. Overall signals of different navigation systems (GPS, GALILEO, GLONASS signals) compose Global Navigation Satellite Systems (GNSS) Signal. Each of the satellite system has separate signal characteristics, but each signal needs to be compatible with the others to prevent interferences and attenuations between signals. The processing of all the signals is performed in same receiver. Hence, complex receiver design is required. In GNSS signals different frequencies are used for different satellite navigation systems such as GPS, Galileo and Glonass. When the group delay response is observed in SAW filters it shows that the signals lie on different frequencies have different delays. Manufacturers carried out measurements with respect to carrier wave but they have ignored the spreading codes or modulation. In this research, we will design a model for GNSS SAW filter in Matlab. This model can be use to obserce the delay of the signals. This model will allow the manufacturers to address these problems in the SAW filter software to optimise slope and magnitude of the design which will benefit the users of GNSS all over the world to get more precise positioning.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3643